052 The prevalence of left atrial appendage thrombus in patients undergoing catheter ablation for atrial fibrillation maintained on warfarin. (16th May 2012) - Herring, N; Page, S P; Ahmed, M; Burg, M; Hunter, R; Earley, M J; Sporton, S C; Bashir, Y; Betts, T R; Schilling, R; Rajappan, K
Abstract : Introduction: Reports of the prevalence of left atrial appendage (LAA) thrombus among patients undergoing catheter ablation for atrial fibrillation (AF) vary and may depend on the anticoagulation regime used prior to the procedure. Methods: We undertook transoesophageal echocardiograms (TOE) in 586 patients (age 59.9±0.4 years old, mean±SE, 64.5% male) undergoing catheter ablation for AF who were anti-coagulated on warfarin (international normalised ratio 2–3) for at least 3 consecutive weeks prior to procedure and maintained on warfarin for the procedure itself. Results: LAA thrombus was identified in 3 patients from 586 (0.5%) despite all 3 having therapeutic INRs (2.2, 2.2 and 3.3 respectively). None of the remaining patients had a peri-procedural stroke. The three patients with LAA thrombus had CHADS2 scores of ≥1 and CHA2DS2-VASc scores of ≥2. All three patients had impaired left ventricular systolic function (LVSF), and LAA emptying velocities of <40 cm/s (23, 29 and 31 cm/s). Patients with LAA emptying velocities <40 cm/s on TOE (n=111) had significantly (p<0.05) higher CHADS2 (0.9±0.1 vs 0.7±0.001) and CHA2DS2-VASc scores (1.7±0.1 vs 1.4±0.1), and larger LA diameter (4.95±0.09 vs 4.38±0.05 cm, OR for LA >4.6 cm: 2.4, 95% CI 2.13 to 5.41), and were more likely to have impaired LVSF (OR: 2.66, 95% CI 1.52 to 4.66) compared to those with higher velocities on multivariate analysis. Conclusions: The prevalence of LAA thrombus using our anticoagulation regime is extremely low. Providing patients have been therapeutically anti-coagulated, pre-operative TOE need only be performed in patients with a CHADS2 score of ≥1/CHA2DS2-VASc score of ≥2 or when LA diameter is >4.6 cm. This criteria has the highest sensitivity (84%) for identifying LAA velocities of <40 cm/s as well as having a sensitivity of 100% for identifying thrombus and also would reduce the number of TOEs performed by 27.7%.